Non-noble metal-based self-supporting electrode, preparation method thereof and application of non-noble metal-based self-supporting electrode in efficient electrolyzed water

By using non-precious metal-based self-supporting electrodes in the ALK electrolytic hydrogen production electrode, and using the heterojunction interface between NiFe unit cell nanoparticles and CoFe LDH, the problem of poor performance of ALK electrolytic hydrogen production technology under high current density is solved, and efficient and stable electrolytic water decomposition is achieved, reducing the cost of hydrogen production.

CN119800431AActive Publication Date: 2025-04-11SUZHOU UNIV OF SCI & TECH

Patent Information

Application Number
CN202510179036.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-04-11
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

ALK electrolytic hydrogen production technology has poor long-term performance at high current density, especially the slow kinetics of oxygen evolution reaction (OER) occurring on the anode, resulting in high hydrogen production costs, limiting its large-scale application.

Method used

Non-precious metal-based self-supporting electrodes, including the transition layer of NiFe unit cell nanoparticles and the catalytic active layer of CoFe LDH, are used to form a heterojunction interface through intermetallic forces, optimize the interface contact between the catalytic active layer and the substrate, and improve the stability and catalytic performance of the electrode.

Benefits of technology

It achieves low oxygen evolution overpotential, high electrical density and excellent stability, reduces the energy consumption of hydrogen production by ALK electrolyzing water, and makes catalysts hope to go from laboratory to commercial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800431A_ABST
    Figure CN119800431A_ABST
Patent Text Reader

Abstract

The invention relates to a non-noble metal-based self-supporting electrode, a preparation method thereof and application of the non-noble metal-based self-supporting electrode in efficient electrolyzed water. The self-supporting electrode comprises a non-noble metal substrate layer, and a transition layer and a catalytic activity layer which are sequentially arranged on the surface of the non-noble metal substrate layer, the transition layer comprises NiFe unit cell nano particles; the catalytic activity layer comprises CoFeLDH, and the CoFeLDH is of a cactus spherical structure formed by a nano needle-shaped array; and a heterojunction interface is arranged between the transition layer containing the NiFe unit cell nanoparticles and the catalytic activity layer containing the CoFeLDH. The catalyst has low oxygen evolution overpotential and has high current density and excellent stability under the working condition, the transition layer is constructed between the catalytic active layer and the foamed nickel substrate, interface contact between the catalytic active layer and the substrate can be optimized, more uniform stress distribution and better interface adhesion can be achieved, charge transfer and mass transfer are enhanced, and the catalytic activity of the catalyst is improved. Therefore, the electrode interface stability is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a non-noble metal-based self-supporting electrode, a preparation method thereof, and application thereof in efficient water electrolysis. Background Art

[0002] Excellent renewable resources such as solar energy, wind energy, and hydropower are insufficient to meet our growing energy needs due to their volatility and intermittency, and their storage and conversion problems need to be solved urgently. Among them, hydrogen energy is considered to be a green energy that can be vigorously developed under the background of carbon neutrality because of its advantages such as ultra-high energy density, sustainability, and zero carbon emissions. At present, the bottleneck restricting the development of hydrogen energy lies in the difficulty of hydrogen preparation and high technical cost. If the cost of hydrogen production is reduced to the level of coal and natural gas, it will be expected to completely solve the global energy crisis. The existing water electrolysis hydrogen production technology has four mainstream technical routes: alkaline (ALK) water electrolysis hydrogen production, proton exchange membrane (PEM) water electrolysis hydrogen production, solid oxide (SOEC) water electrolysis hydrogen production, and anion exchange membrane (AEM) water electrolysis hydrogen production. Compared with other electrolyzer technologies, the maximum production capacity of ALK single tank is 1,500 standard cubic meters. Compared with PEM, it has a longer service life and lower annual maintenance costs. Therefore, the investment cost and service life determine that ALK is the most suitable for large-scale water electrolysis hydrogen production applications.

[0003] However, the practical application of ALK water electrolysis to produce hydrogen is still challenged by slow reaction kinetics and poor long-term performance at high current density. Compared with the hydrogen evolution reaction (HER) occurring at the cathode, the oxygen evolution reaction (OER) occurring at the anode involves a four-electron transfer process, which has a slower kinetic process and is the rate-determining step of the water electrolysis reaction. Therefore, to realize the commercialization of ALK water electrolysis to produce hydrogen, it is necessary to design and develop efficient catalysts to reduce the OER reaction energy barrier. However, the precious metal catalysts currently used in the commercial industry are expensive and scarce, which seriously hinders their large-scale application in ALK water electrolysis to produce hydrogen. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a non-precious metal-based self-supporting electrode and a preparation method thereof and its application in efficient water electrolysis. The self-supporting alkaline water electrolysis electrode obtained by the present invention has a low oxygen evolution overpotential and has high electric density and excellent stability under working conditions. The preparation method is simple and controllable, low-cost, and the electrode has excellent performance, which can be expanded to practical industrial applications.

[0005] The first object of the present invention is to provide a non-precious metal-based self-supporting electrode, comprising a non-precious metal substrate layer, and a transition layer and a catalytic active layer sequentially arranged on the surface of the non-precious metal substrate layer;

[0006] The transition layer includes NiFe unit cell nanoparticles;

[0007] The catalytic active layer includes CoFe LDH, and the CoFeLDH is composed of a nano-needle array and presents a cactus ball-like morphology;

[0008] A heterojunction interface is formed between the transition layer containing NiFe unit cell nanoparticles and the catalytic active layer containing CoFe LDH through intermetallic forces.

[0009] In some embodiments of the present invention, the pore sizes of the transition layer and the catalytically active layer increase from small to large from the transition layer to the catalytically active layer;

[0010] The non-noble metal substrate layer includes foamed nickel, nickel felt, foamed nickel iron, foamed copper or carbon paper.

[0011] In some embodiments of the present invention, the thickness of the transition layer is 0.5-1 μm; the thickness of the catalytic active layer is 10-15 μm.

[0012] The second object of the present invention is to provide a method for preparing the non-noble metal-based self-supporting electrode, comprising the following steps:

[0013] Providing a pretreated non-precious metal substrate and a metal seed solution obtained by mixing a nickel salt solution and an iron salt solution;

[0014] Placing a non-precious metal substrate in the metal seed solution, and in-situ etching the surface of the metal substrate to generate NiFe crystal cell nanoparticles to form a transition layer;

[0015] dissolving cobalt salt, iron salt, inducer and surfactant in a solvent to obtain a pre-solution;

[0016] The metal substrate with a transition layer formed on the surface is subjected to a hydrothermal reaction in a pre-solution to obtain a CoFeLDH nano-needle array supported on the NiFe crystal cell nanoparticles to form a catalytic active layer, thereby obtaining a non-precious metal-based self-supporting electrode.

[0017] In some embodiments of the present invention, the non-precious metal substrate is degreased and the surface oxide layer is treated. The treatment process includes acid treatment, water washing, and vacuum drying of the non-precious metal substrate in sequence. The acid used in the acid treatment is hydrochloric acid with a concentration of 4-5wt%.

[0018] In some embodiments of the present invention, the nickel source in the nickel salt solution is selected from one or more of nickel nitrate hexahydrate, nickel chloride, nickel acetate or nickel sulfate, and the concentration of the nickel source solution is 0.05 to 0.8 mol / L, illustratively, it can be 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, etc., or any interval value between any two values;

[0019] The iron salt in the iron salt solution is selected from one or more of ferrous sulfate heptahydrate, ferrous chloride or ferrous nitrate; the concentration of the iron salt solution is 0.05-0.2 mol / L, illustratively, it can be 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, etc., or any interval value between any two values;

[0020] The molar ratio of the nickel salt to the iron source is (1:1) to (4:1), and illustratively, can be 1:1, 2:1, 3:1, 4:1, etc., or any interval value between any two values.

[0021] Furthermore, after the NiFe crystal cell nanoparticles are generated on the surface of the non-precious metal substrate, they are rinsed with deionized water and ethanol in sequence for multiple times and placed in a vacuum drying oven for drying.

[0022] In some embodiments of the present invention, the in-situ etching conditions are: room temperature 25° C., and a standing time of not less than 2 hours. Furthermore, the standing time is preferably 24 hours.

[0023] In some embodiments of the present invention, the cobalt salt is selected from one or more of cobalt nitrate hexahydrate, cobalt acetate or cobalt chloride;

[0024] The iron salt is selected from one or more of ferric nitrate nonahydrate, ferric sulfate or ferric chloride;

[0025] The inducer is selected from one or more of urea, sodium hydroxide or ammonia water;

[0026] The surfactant is selected from one or more of ammonium fluoride, disodium ethylenediaminetetraacetate, hexadecyltrimethylammonium bromide, or sodium dodecylsulfonate.

[0027] In some embodiments of the present invention, the concentration of the iron salt is 0.003-0.015 mol / L, and illustratively, it can be 0.003 mol / L, 0.005 mol / L, 0.010 mol / L, 0.015 mol / L, or any interval value between any two values; the concentration of the cobalt salt is 0.015-0.15 mol / L, and illustratively, it can be 0.015 mol / L, 0.02 mol / L, 0.025 mol / L, 0.03 mol / L, 0.035 mol / L, 0.040 mol / L, 0.045 mol / L, 0.05 mol / L, 0.055 mol / L, 0.060 mol / L, 0.065 mol / L, 0.070 mol / L, 0.075 mol / L, 0.080 mol / L, 0.085 mol / L, 0.090 mol / L, 0.095mol / L, 0.10mol / L, 0.15mol / L, or any interval between any two values; the concentration of the inducer is 0.025-0.25mol / L, and illustratively, it can be 0.025mol / L, 0.030mol / L, 0.040mol / L, 0.05mol / L, 0.06mol / L, 0.07mol / L, 0.08mol / L, 0.09mol / L, 0.1mol / L, 0.15mol / L, 0.20mol / L, 0.25mol / L, etc., or any interval between any two values; the concentration of the surfactant is 0.05-0.5mol / L, and illustratively, it can be 0.05, 0.10, 0.15, 0.2, 0.3, 0.35, 0.4, 0.45, 0.5, etc., or any interval between any two values.

[0028] The molar ratio of the iron salt, the cobalt salt, the inducer and the surfactant is (1:1:9:18) to (1:10:9:18).

[0029] In some embodiments of the present invention, the conditions of the hydrothermal reaction are as follows: the hydrothermal reaction temperature is 100-150° C., and the reaction time is 2 to 24 hours.

[0030] Furthermore, after the growth of the CoFeLDH nanoneedle array, it was rinsed with deionized water and ethanol in sequence for multiple times and placed in a vacuum drying oven for drying to obtain a finished electrode.

[0031] The third object of the present invention is to provide a device for efficient water electrolysis, comprising the non-precious metal-based self-supporting electrode.

[0032] The above technical solution of the present invention has the following advantages compared with the prior art:

[0033] 1. A NiFe crystal cell transition layer is generated by in-situ etching. A transition layer is constructed between the catalytic active layer and the nickel foam substrate, which can optimize the interface contact between the catalytic active layer and the substrate, help achieve more uniform stress distribution and better interface adhesion, enhance charge transfer and mass transfer, and thus achieve catalyst interface stability.

[0034] 2. A simple hydrothermal synthesis method was used to grow the CoFeLDH catalytic active layer on the NiFe crystal cell transition layer. CoFeLDH exhibited a unique cactus-like structure composed of a needle array and had abundant active sites, which greatly increased the specific surface area of ​​the catalyst and increased the mass transfer capacity.

[0035] 3. During the water electrolysis process, the strong interaction between the NiFe unit cell transition layer and CoFeLDH will lead to electron transfer at the interface. The Mott-Schottky heterojunction can also induce special interface effects such as electronic coupling and defects, thereby optimizing the adsorption / desorption behavior of the catalyst for various reaction intermediates, increasing the number of reaction sites, and improving the electrocatalytic performance.

[0036] 4. CoFeLDH / NiFe-NF has faster reaction kinetics than single-phase NiFe-NF or CoFeLDH-NF, and exhibits excellent high current density and low overpotential, as well as relatively excellent high current stability in an electrolytic cell under simulated working conditions.

[0037] 5. The pore gradient transition layer of CoFeLDH / NiFe-NF increases the structural stability. The dual-phase heterojunction interface induces the formation of a built-in electric field to accelerate the transfer of space charge, stabilize the synergistic effect between metals, and comprehensively optimize the OER catalytic activity and high current density durability of ALK water electrolysis from macrostructure to microstructure, thereby reducing the energy consumption of ALK water electrolysis, making it possible for CoFeLDH / NiFe-NF catalyst to achieve the transition from laboratory to commercial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0039] Figure 1 1 and 2 are SEM images of comparative examples and embodiments of the present invention; wherein, (a) comparative example 1, (b) comparative example 2, and (c) embodiment 1.

[0040] Figure 2 This is a TEM image of Example 1 of the present invention.

[0041] Figure 3 It is the XRD diagram of the comparative example and the embodiment of the present invention.

[0042] Figure 4 1 and 1 are (a) specific surface area diagrams and (b) pore size distribution diagrams of comparative examples and embodiments of the present invention.

[0043] Figure 5 These are XPS high-resolution images of the comparative examples and embodiments of the present invention, including (a) a high-resolution image of Ni2p orbital, (b) a high-resolution image of Co2p orbital, and (c) a high-resolution image of O1s orbital.

[0044] Figure 6 1. The (a) LSV curve, (b) Tafel curve, and (c) stability curve of the comparative example and the embodiment of the present invention.

[0045] Figure 7 (a) Nyquist diagram, (b)-(d) Bode diagrams of comparative examples and embodiments of the present invention.

[0046] Figure 8 1. (a) Current density-voltage relationship curve diagram of the embodiment of the present invention and the comparative example, (b) operating time-voltage relationship curve diagram of embodiment 3.

[0047] Fig. 9 1 and 2 are SEM images of the comparative examples and embodiments of the present invention after oxygen evolution testing, wherein (a) is comparative example 1, (b) is comparative example 2, and (c) is embodiment 1. DETAILED DESCRIPTION

[0048] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0049] The embodiment of the high-efficiency oxygen evolution non-precious metal-based self-supporting alkaline water electrolysis electrode of the present invention comprises nickel foam, NiFe crystal cell nanoparticles grown on the nickel foam, and the NiFe crystal cell nanoparticles are covered with CoFeLDH nano needle arrays. The NiFe crystal cell nanoparticle transition layer is not only tightly combined with the nickel foam substrate, but also closely connected with the CoFe LDH catalytic active layer. The NiFe crystal cell nanoparticle transition layer provides good adhesion between the catalyst and the substrate, increases the structural stability of the catalyst, and the CoFe LDH catalytic active layer provides a large specific surface area for the catalyst, increases the active sites, and increases the catalyst mass transfer. There is a heterojunction interface between the NiFe crystal cell nanoparticle transition layer and the CoFe LDH catalytic active layer, which induces the formation of a built-in electric field to accelerate the transfer of space charges, thereby improving the intrinsic catalytic activity of the electrode.

[0050] Specifically, the water electrolysis electrode prepared in the present application is described in detail with the following multiple comparative examples and embodiments.

[0051] Comparative Example 1:

[0052] This comparative example provides a method for preparing a Ni-based self-supporting electrode by in-situ etching a NiFe transition layer on nickel foam, comprising the following steps:

[0053] (1) A commercial nickel foam with a thickness of 0.3 mm was cut into 2 cm*2 cm pieces, placed in 4 wt% hydrochloric acid for ultrasonic treatment for 30 min, then rinsed with deionized water until neutral, then ultrasonicated with deionized water for 10 min, then replaced with clean deionized water for ultrasonic treatment for 20 min, and finally ultrasonicated with anhydrous ethanol for 30 min, placed in a vacuum drying oven at 60°C, and dried for 12 h for later use.

[0054] (2) 20 mmol of Ni(NO3)2·6H2O was dissolved in 100 mL of isopropanol and ultrasonicated for 30 min to form solution A. 3 mmol of FeSO4·7H2O was stirred and dissolved in 33 mL of deionized water and stirred for 5 min to form solution B.

[0055] (3) Pour solution B into solution A, mix and stir for 1 min to obtain a mixed solution, quickly immerse the 2 cm*2 cm nickel foam that has been pretreated in step (1) into the mixed solution, let it stand at room temperature for 24 h, take out the nickel foam and rinse it with deionized water, then rinse the nickel foam with anhydrous ethanol, put it in a vacuum drying oven, and dry it at 60°C for 12 h to obtain a nickel foam with an in-situ etched NiFe transition layer.

[0056] Comparative Example 2:

[0057] This comparative example provides a method for preparing a Ni-based self-supporting electrode by hydrothermally synthesizing CoFeLDH cactus balls on nickel foam, comprising the following steps:

[0058] (1) A commercial nickel foam with a thickness of 0.3 mm was cut into 2 cm*2 cm pieces, placed in 4 wt% hydrochloric acid for ultrasonic treatment for 30 min, then rinsed with deionized water until neutral, then ultrasonicated with deionized water for 10 min, then replaced with clean deionized water for ultrasonic treatment for 20 min, and finally ultrasonicated with anhydrous ethanol for 30 min, placed in a vacuum drying oven, and dried at 60°C for 12 h for use.

[0059] (2) 1.5 mmol of Co(NO3)2·6H2O, 0.3 mmol of Fe(NO3)3·9H2O, 2.7 mmol of urea and 5.6 mmol of ammonium fluoride were dissolved in 35 mL of deionized water and stirred for 10 min to form a mixed solution.

[0060] (3) Immerse the 2 cm*2 cm nickel foam that has been pretreated in step (1) into the mixed solution obtained in step (2), transfer the mixed solution to a 50 mL polytetrafluoroethylene-lined reactor, place it in a forced air drying oven, and react at 120° C. for 10 h. After the temperature drops to room temperature, take out the nickel foam, rinse it with deionized water, and then rinse the nickel foam with anhydrous ethanol, place it in a vacuum drying oven, and dry it at 60° C. for 12 h to obtain a nickel foam with CoFeLDH cactus balls grown on the surface.

[0061] Comparative Example 3:

[0062] A piece of comparative example 1 was cut into 2cm*2cm and used as the anode. A commercial Raney nickel electrode was selected as the cathode and a commercial composite diaphragm was selected as the diaphragm. They were assembled in an electrolytic cell fixture. The electrolyte was 30wt% KOH solution. The voltage of the electrolytic cell fixture was tested at 80°C under different current densities.

[0063] Comparative Example 4

[0064] A piece of comparative example 2 was cut into 2cm*2cm and used as the anode. A commercial Raney nickel electrode was selected as the cathode and a commercial composite diaphragm was selected as the diaphragm. They were assembled in an electrolytic cell fixture. The electrolyte was 30wt% KOH solution. The voltage of the electrolytic cell fixture was tested at 80°C under different current densities.

[0065] Embodiment 1:

[0066] This embodiment provides a method for preparing a highly efficient oxygen evolution non-precious metal Ni-based self-supporting electrode, as shown below:

[0067] (1) A commercial nickel foam with a thickness of 0.3 mm was cut into 2 cm*2 cm pieces, placed in 4 wt% hydrochloric acid for ultrasonic treatment for 30 min, then rinsed with deionized water until neutral, then ultrasonicated with deionized water for 10 min, then replaced with clean deionized water for ultrasonic treatment for 20 min, and finally ultrasonicated with anhydrous ethanol for 30 min, placed in a vacuum drying oven, and dried at 60°C for 12 h for use.

[0068] (2) 20 mmol of Ni(NO3)2·6H2O was dissolved in 100 mL of isopropanol and ultrasonicated for 30 min to form solution A. 3 mmol of FeSO4·7H2O was stirred and dissolved in 33 mL of deionized water and stirred for 5 min to form solution B.

[0069] (3) Pour solution B into solution A, mix and stir for 1 min to obtain a mixed solution, quickly immerse the 2 cm*2 cm nickel foam that has been pretreated in step (1) into the above mixed solution, let it stand at room temperature for 24 h, take out the nickel foam, rinse it with deionized water, then rinse it with anhydrous ethanol, put it in a vacuum drying oven, dry it at 60°C for 12 h, and set it aside to obtain a nickel foam with an in-situ grown NiFe crystal cell transition layer.

[0070] (4) 1.5 mmol of Co(NO3)2·6H2O, 0.3 mmol of Fe(NO3)3·9H2O, 2.7 mmol of urea and 5.6 mmol of ammonium fluoride were dissolved in 35 mL of deionized water and stirred for 10 min to form a mixed solution.

[0071] (5) Immerse the nickel foam with the in-situ grown NiFe crystal cell transition layer obtained in step (3) into the mixed solution obtained in step (4), transfer the mixed solution to a 50 mL polytetrafluoroethylene liner reactor, place it in a forced air drying oven, and react at 120° C. for 10 h. After the temperature drops to room temperature, take out the nickel foam, rinse it with deionized water, and then rinse it with anhydrous ethanol, place it in a vacuum drying oven at 60° C., and dry it for 12 h to obtain a highly efficient oxygen evolution non-precious metal Ni-based self-supporting electrode.

[0072] Embodiment 2:

[0073] Example 1 was cut into 2cm*2cm pieces and used as the anode. A commercial Raney nickel electrode was selected as the cathode and a commercial composite membrane Agfa220 was selected as the diaphragm. The electrodes were assembled in an electrolytic cell fixture. The electrolyte was a 30wt% KOH solution. The voltage of the electrolytic cell fixture was tested at 80°C under different current densities. The experimental results are shown in Table 4 and Figure 8 .

[0074] Embodiment 3:

[0075] Two nickel foam electrodes obtained in Example 1 were cut into 2 cm*2 cm pieces and used as anode and cathode respectively. The commercial composite membrane Agfa220 was selected as the diaphragm. They were assembled in an electrolytic cell fixture. The electrolyte was 30 wt% KOH solution. The electrolyte was 3000 A / m at 80 °C. 2 The long-term stability test and start-stop experiment were carried out at the current density of , and the change curve of the clamp voltage over time was recorded. The experimental results are shown in Table 4 and Figure 8 .

[0076] In order to clearly observe the structure and morphology of the synthesized electrode and its formation process, SEM and TEM characterization techniques were used to analyze the morphology of the NiFe-NF electrode with NiFe crystal cell nanoparticles grown on nickel foam, the CoFeLDH-NF electrode with CoFeLDH nanoneedle arrays grown on nickel foam, and the final CoFeLDH / NiFe-NF electrode with a transition layer. Figure 1 Figures ac show the SEM images of the Ni-based self-supporting electrodes prepared in Comparative Example 1, Comparative Example 2 and Example 1, respectively. Figure 1 As can be seen in a, the electrode of comparative example 1 is a fusiform unit cell particle grown on the nickel foam, forming a uniform and dense nanolayer; Figure 1 As shown in b, it can be seen that the electrode of comparative example 2 is a layer of nanosheet array grown on nickel foam, and the top of the array is a slender nanoneedle. The nanoneedles gather together to form thorn-like cacti, which greatly increases the specific surface area of ​​the electrode. The change of the array from nanosheets to nanoneedles is conducive to the transmission of charges; Figure 1 The electrode obtained in Example 1 is shown in Figure c. It can be seen that the electrode surface is evenly covered with thorny cacti, indicating that the CoFeLDH grown on the NiFe nanolayer can grow more evenly. Figure 2 It can be confirmed from the TEM image of Example 1 that the thorny cactus CoFeLDH grown on the surface is composed of nanosheets and nanoneedles. The structural characterization results of the electrode show that the presence of the nano transition layer can increase the binding force between CoFeLDH and the nickel foam substrate, which is conducive to further increasing the specific surface area and the exposure of active sites.

[0077] In order to better understand the evolution of the crystal structure during the electrode synthesis process, XRD characterization technique was used for further analysis. Figure 3 As shown, the crystallinity of the electrodes of Comparative Example 1, Comparative Example 2 and Example 1 is very excellent, which is completely matched with the standard card, proving the successful growth of NiFe and CoFeLDH. In Example 1, it can be seen that the peak intensity of NiFe is weakened, which is due to the growth of CoFeLDH covering part of the NiFe signal. From the N2 adsorption-desorption isotherm and pore size distribution diagram, it can be seen that ( Figure 4 In the graph of ab), the specific surface area of ​​the electrode NiFe-NF in comparative example 1 is the smallest, and the specific surface area of ​​the electrode CoFeLDH / NiFe-NF in embodiment 1 is the largest. The specific values ​​can be found in Table 1. It was determined that the specific surface area of ​​the electrode in embodiment 1 is 24.398 m 2 g -1 The mesoporous nature can be seen from the pore size analysis, and the maximum porosity is 0.037cc g -1 The high specific surface area and large porosity can provide abundant active areas between the electrode and the electrolyte, which is beneficial to the migration of electrons.

[0078] The electronic structure of the catalyst will directly affect the electrochemical reaction, so the surface chemical state of the catalyst was studied by XPS testing. Figure 5 As shown in a, the Ni 2p binding energy position in CoFeLDH / NiFe-NF has a significant positive shift (0.33 eV), which is due to the formation of the heterojunction regulating the electronic configuration around Ni, reducing the electron density around it. 3+ / Ni 2+ The peak areas of CoFeLDH / NiFe-NF are 0.46 and 0.25, respectively (Table 2), indicating that the Ni 3+ The content increases, which is due to the decrease of electron density around Ni. 2+ Oxidized to Ni 3 + .like Figure 5 As shown in Figure b, compared with the Co 2p orbital of CoFeLDH-NF, the Co 2p binding energy of CoFeLDH / NiFe-NF also showed a significant negative shift (0.52 eV), indicating that the electron cloud density around Co 2p increased. 3+ / Co 2+ The peak areas of the NiFe and CoFeLDH are 1.42 and 3.1, respectively (Table 2), indicating that after the heterojunction is formed, electrons are transferred from NiFe to CoFeLDH, thereby increasing the electron cloud density around Co and resulting in a large amount of Co 3+ Reduced to Co 2+ In Example 1, the electrons are transferred from NiFe to CoFeLDH, thereby optimizing the electronic structure of the heterogeneous interface and helping to improve the OER activity. Figure 5 The high-resolution spectrum of O1s shown in c can be fitted into three main peaks at 529.75 eV, 531.41 eV and 532.47 eV. L ), surface active oxygen vacancies (O V ) and surface physically adsorbed oxygen (O C ). According to the peak area ratio, O L is 4.31%, V The oxygen vacancies in CoFeLDH-NF are 69.96%, which is more than that in NiFe-NF (Table 2). The oxygen vacancies in CoFeLDH-NF are the largest, indicating that the generation of CoFeLDH can introduce a large number of oxygen vacancies, which is beneficial to the adsorption of OH- on the electrode surface, thereby effectively improving the OER reaction activity.

[0079] Regarding the alkaline oxygen evolution (OER) performance test and impedance (EIS) test, an electrocatalytic oxygen evolution test was performed in a standard three-electrode system using 1.0M KOH as the electrolyte to study the effect of the heterojunction interface on the OER performance. The working electrode was the electrode prepared in Comparative Examples 1-2 and Example 1, the counter electrode was a graphite rod, and the reference electrode was a Hg / HgO electrode, which was placed in a 1 mol / L KOH electrolyte at room temperature (25°C). An Autolab electrochemical workstation was used for cyclic voltammetry (CV) activation, and the working electrode was activated at a voltage range of -1.6 to 0.9 V vs. RHE at 50 mV s -1 The activation was cycled 30 times at a scan rate of . In order to avoid the interference of the oxidation peak, all linear sweep voltammetry (LSV) tests were performed by negative scanning, and the test voltage range was 0-1.1V vs. RHE. EIS was performed in the range of 100kHz to 0.01Hz, with an AC potential amplitude of 5mV. The in-situ impedance Bode diagram was obtained in the voltage range of 0-0.6V.

[0080] LSV curve Figure 6 As shown in a, it can be seen that the current density that can be achieved in Example 1 is the highest, and only an overpotential of 218 mV is required to reach 100 Am -2 The current density is lower than the overpotential required for Comparative Example 1 (230mV) and Comparative Example 2 (258mV) (Table 4). This shows that the presence of the transition layer greatly improves the OER performance, and CoFeLDH can improve the OER performance at a large current density, and the synergistic effect of the heterojunction interface further improves the OER performance. In addition to the overpotential being able to illustrate the catalytic performance of the electrode, the Tafel slope is also used to characterize the speed of the reaction kinetics in the OER process. The smaller the Tafel slope, the faster the reaction kinetics. The Tafel slopes of Example 1, Comparative Example 1 and Comparative Example 2 are 47.7, 61.1 and 80.4mV dec, respectively. -1 ( Figure 6 (b), indicating that Example 1 has a better electrocatalytic activity, indicating that the heterojunction between the NiFe active layer and the CoFeLDH can significantly improve the OER reaction kinetics. The stability of the electrode is very important in practical applications. -2 At a current density of , the electrode of Example 1 can be maintained for 250 h without obvious attenuation ( Figure 6 The LSV curves before and after the continuous stability test were also recorded. The final LSV curve was slightly attenuated in the OER region compared to the initial LSV ( Figure 6 (as shown in the illustration in c), indicating that the electrode of Example 1 has very excellent stability.

[0081] In electrocatalysis, the electron transfer rate is also very important for performance, and electrochemical impedance spectroscopy can be used to further study the OER kinetics of different catalysts. Figure 7 The Nyquist diagram in a is obtained by testing at 1.524V (vs. RHE). All points obtained by testing are based on the equivalent circuit diagram ( Figure 7 (shown in the illustration in a) can be fitted into three parts, including the electrolyte impedance R s And the charge transfer resistance R ct =R ct1 +R ct2 (See Table 3). The charge transfer impedance of Example 1 is the smallest at 0.422Ω, that of Comparative Example 1 is 0.573Ω, and that of Comparative Example 2 is 0.713Ω, indicating that electrons are transferred very quickly in the three electrodes, and the electrodes have good mass transfer capacity and electrical conductivity. The transfer is fastest in CoFeLDH / NiFe-NF, and faster electron transfer can effectively improve the catalytic performance. Since the electrocatalytic oxygen evolution process is usually accompanied by the reconstruction of the catalyst, the speed at which the catalyst reconstruction is completed will also affect the performance of OER. In order to further explore the effect of the synergistic effect between the NiFe active layer and CoFeLDH on the performance of the composite material and the interface action process, the Bode diagram of the synthesized catalyst was further analyzed in detail. Figure 7 As shown in (b)-(d), the Bode diagram obtained by in-situ EIS test of all electrodes can be divided into two stages according to high and low frequencies: first, the electro-oxidation process of the catalyst in the HF region, at which stage the catalyst completes surface oxidation reconstruction, and the interface corresponding to this stage is the interface between the catalyst and the DDL. After the surface reconstruction is completed, the OER process begins, which occurs at the LF region interface formed between the reconstructed catalyst and the DDL. It can be judged that between 0.924-1.274V, the phase angle of the electrode in Example 1 in the high-frequency region begins to decrease, and oxidation reconstruction occurs on the surface, and no obvious current is generated at this stage. When the potential reaches 1.299V, the oxidation is completed, and the phase angle turns from the high-frequency region to the low-frequency region, which means the beginning of the OER process, and the current begins to increase significantly at this time. And as the potential increases, the phase angle in the low-frequency region also gradually decreases, indicating that a violent OER process has begun to occur. Similarly, the potentials at which surface oxidation reconstruction is completed in the electrodes of Comparative Example 1 and Comparative Example 2 are 1.374 V and 1.399 V, respectively, indicating that the oxidation process is slow, thereby increasing the starting potential of OER. According to the analysis of the results, it is further proved that there is a synergistic effect between the NiFe active layer and CoFeLDH, which can promote electrode surface reconstruction, improve reaction kinetics, and reduce the starting potential of OER.

[0082] Regarding the electrolytic cell test, the CoFeLDH / NiFe-NF composite electrode obtained in Example 1 was cut into 2cm*2cm as the anode, and a commercial Raney nickel electrode was selected as the cathode; a commercial composite diaphragm was selected as the diaphragm, which was assembled in the electrolytic cell test device, the electrolyte was 30wt% KOH solution, the temperature was 80℃, and the voltage of the electrolytic cell device was measured at different current densities. Figure 8 As shown in a, at 3000A / m 2 At the current density of 10000A / m, the voltages of the assembled electrolytic cells of Example 2, Comparative Example 3 and Comparative Example 4 were 1.68V, 1.723V and 1.725V respectively; 2 Under the current density, the assembled electrolytic cell voltages of Example 2, Comparative Example 3 and Comparative Example 4 were 1.898V, 1.988V and 2.028V respectively. Stability test, two 2cm*2cm CoFeLDH / NiFe-NF electrodes were used as cathode and anode respectively, and the diaphragm was a commercial composite diaphragm, which was assembled in the electrolytic cell test device, the electrolyte was 30wt% KOH solution, the temperature was 80℃, and the current was 3000A / m 2 The electrolytic cell was operated for 176 h at the current density and started and stopped every 8 h, and the voltage of the electrolytic cell was recorded. Figure 8 As shown in Fig. b, the voltage retention rate of Example 3 can reach 90.4% at 175h, indicating that the CoFeLDH / NiFe-NF electrode still has good stability at industrial current density. In order to investigate the structural stability of the CoFeLDH / NiFe-NF electrode material, the electrode after the OER test was characterized by SEM, as shown in Fig. Fig. 9 As shown in (a)-(c), it can be seen that the NiFe active layer on the surface of the electrode of Comparative Example 1 falls off significantly, the electrode of Comparative Example 2 has a certain amount of falling off, and there is almost no falling off on the surface of the electrode of Example 1, which once again proves that the growth of CoFeLDH in the example is conducive to the improvement of the stability of the electrode structure, and the interaction between the NiFe active layer and CoFeLDH can further improve the electrode stability. In short, the present invention constructs a transition layer between the catalytic active layer and the nickel foam substrate to optimize the OER performance of water electrolysis, and the present invention can greatly improve the structural stability of the electrode under working conditions, providing a feasible strategy for designing efficient non-precious metal-based self-supporting alkaline water electrolysis electrodes.

[0083] Table 1 BET specific surface area, pore size distribution and pore volume of the electrodes obtained in the comparative examples and embodiments of the present invention

[0084]

[0085] Table 2 XPS peak areas of comparative examples and embodiments of the present invention

[0086]

[0087]

[0088] Table 3 Resistance values ​​calculated by electrochemical impedance spectroscopy of comparative examples and embodiments of the present invention (Rs: electrolyte resistance; Rct: charge transfer resistance)

[0089]

[0090] Table 4 Oxygen evolution performance of comparative examples and embodiments of the present invention

[0091]

[0092] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A non-precious metal-based self-supporting electrode, characterized in that: It comprises a non-precious metal substrate layer, and a transition layer and a catalytic active layer sequentially arranged on the surface of the non-precious metal substrate layer; The transition layer includes NiFe unit cell nanoparticles; The catalytic active layer includes CoFe LDH, which is composed of a nano-needle array and presents a cactus ball-like morphology; A heterojunction interface is formed between the transition layer containing NiFe unit cell nanoparticles and the catalytic active layer containing CoFe LDH through intermetallic forces.

2. The non-precious metal-based self-supporting electrode according to claim 1, characterized in that: The non-noble metal substrate layer includes foamed nickel, nickel felt, foamed nickel iron, foamed copper or carbon paper.

3. The non-precious metal-based self-supporting electrode according to claim 1, characterized in that: The thickness of the transition layer is 0.5-1 μm; the thickness of the catalytic active layer is 10-15 μm.

4. A method for preparing a non-noble metal-based self-supporting electrode as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: Providing a pretreated non-precious metal substrate and a metal seed solution obtained by mixing a nickel salt solution and an iron salt solution; Placing a non-precious metal substrate in the metal seed solution, and in-situ etching the surface of the metal substrate to generate NiFe crystal cell nanoparticles to form a transition layer; dissolving cobalt salt, iron salt, inducer and surfactant in a solvent to obtain a pre-solution; The metal substrate with a transition layer formed on the surface is subjected to a hydrothermal reaction in a pre-solution to obtain a CoFeLDH nano-needle array supported on the NiFe crystal cell nanoparticles to form a catalytic active layer, thereby obtaining a non-precious metal-based self-supporting electrode.

5. The preparation method according to claim 4, characterized in that: The nickel source in the nickel salt solution is selected from one or more of nickel nitrate hexahydrate, nickel chloride, nickel acetate or nickel sulfate, and the concentration of the nickel source solution is 0.05-0.8 mol / L; The iron salt in the iron salt solution is selected from one or more of ferrous sulfate heptahydrate, ferrous chloride or ferrous nitrate; the concentration of the iron salt solution is 0.05-0.2 mol / L; The molar ratio of the nickel salt to the iron source is (1:1) to (4:1).

6. The preparation method according to claim 4, characterized in that: In-situ etching conditions: room temperature 25°C, standing time not less than 2 hours.

7. The preparation method according to claim 4, characterized in that: The cobalt salt is selected from one or more of cobalt nitrate hexahydrate, cobalt acetate or cobalt chloride; The iron salt is selected from one or more of ferric nitrate nonahydrate, ferric sulfate or ferric chloride; The inducer is selected from one or more of urea, sodium hydroxide or ammonia water; The surfactant is selected from one or more of ammonium fluoride, disodium ethylenediaminetetraacetate, hexadecyltrimethylammonium bromide, or sodium dodecylsulfonate.

8. The preparation method according to claim 4, characterized in that: The concentration of the iron salt is 0.003-0.015 mol / L, the concentration of the cobalt salt is 0.015-0.15 mol / L, the concentration of the inducer is 0.025-0.25 mol / L, and the concentration of the surfactant is 0.05-0.5 mol / L; The molar ratio of the iron salt, the cobalt salt, the inducer and the surfactant is (1:1:9:18) to (1:10:9:18).

9. The preparation method according to claim 4, characterized in that: Conditions of hydrothermal reaction: hydrothermal reaction temperature is 100-150°C, and reaction time is 2 to 24 hours.

10. A highly efficient water electrolysis device, characterized in that: The invention comprises the non-noble metal-based self-supporting electrode as described in any one of claims 1 to 3.

Citation Information

Patent Citations

  • Nano thin sheet assembled nickel-iron hydroxide multistage microspheres and preparation method thereof

    CN105016399A

  • Preparation method of iron-nickel hydrotalcite structure nanosheet for oxygen evolution reaction

    CN106450349A

  • Application of nano heterojunction ferronickel material

    CN118792691A

  • Self-supporting alloy catalytic electrode with three-dimensional porous structure and preparation method of self-supporting alloy catalytic electrode

    CN118880408A

  • Nickel-iron-oxide thin films as an electrocatalyst for water oxidation

    US20240417871A1

Cited By

  • Construction and application of biosensor based on efficient antifouling interface and dual signal amplification

    CN121298854A

  • Nickel-iron-cobalt-based self-supporting oxygen evolution electrode and preparation and application thereof

    CN121760000A

  • Ferronickel-based self-supporting oxygen evolution electrode and preparation method thereof

    CN121874851A